本文共 551 字,大约阅读时间需要 1 分钟。
若矩阵A满足 A + A T = I A+A^{\rm{T}}=I A+AT=I,则A可逆。
反证法。假设A不可逆,则
∃ x 0 ≠ 0 \exists{x_0}\ne0 ∃x0=0,使得 A x 0 = 0 A{x_0}=0 Ax0=0,则 x 0 A T = ( A x 0 ) T = 0 T {x_0}{A^{\rm{T}}} = {(A{x_0})^{\rm{T}}} = {0^{\rm{T}}} x0AT=(Ax0)T=0T∴ 0 ≠ x 0 T x 0 = x 0 T ( A + A T ) x 0 = x 0 T A x 0 + x 0 T A T x 0 = x 0 T 0 + 0 T x 0 = 0 \therefore 0 \ne x_0^{\rm{T}}{x_0} = x_0^{\rm{T}}(A + {A^{\rm{T}}}){x_0} = x_0^{\rm{T}}A{x_0} + x_0^{\rm{T}}{A^{\rm{T}}}{x_0} = x_0^{\rm{T}}0 + {0^{\rm{T}}}{x_0} = 0 ∴0=x0Tx0=x0T(A+AT)x0=x0TAx0+x0TATx0=x0T0+0Tx0=0
矛盾,所以A可逆。
转载地址:http://fulnz.baihongyu.com/